RESPON PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogaea L) TERHADAP JARAK TANAM DAN ASAL BIJI PADA POLONG - Darmawati Jayasumarta (AGRIUM: Jurnal Ilmu Pertanian, 2012)
AbstractResponse of growth and production in peanuts (Arachis hypogae) on seed spacing and origin of the pods have been investigated. The study was designed according to the Random Design (RAK) factorial with two factors studied. Jark cropping factor as the first treatment factors. Spacing factor (J) consists of two levels, namely J1 = 30cm x 20cm, 30cm x 30cm = J2, J3 = 20cm x 20cm. While the origin of seed treatment factors on pod (P) consists of three levels, namely P1 (1per plor seed pods), P2 (second seed pods per plot), P3 (third seed pods per plot). The entire unit test in repeated sebamyak 3 times. Parameter observations used in this study include plant height, number of primary branches, number of empty pods per plant, production per plot, weight of wet pods per plant, dry weight of pods per plant and number of seeds per pod. Based on the observations and the origin of seed spacing on pod gives a significantly different effect parameters plant height, number of primary branches, number of empty pods per plant, production per plot, the wet weight of pods per plant, and dry weight of pods per plant. While the parameters of the number of seeds per pod were not significantly different.Keywords: Peanut, seed spacing, origin of the pods